STRATEGI PENANGGULANGAN IUU FISHING DI WILAYAH PERAIRAN KABUPATEN POHUWATO - Alwi, Kamri; Alwi, Muhammad Jamal; Danial, Danial (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2021)
This study aims to formulate policies by the government in controlling IUU in the waters of Pohuwato Regency. The method used in this research is the interview method, the distribution of questionnaires, documentation and direct observation which is supported by two data, namely primary and secondary data. Determination of respondents is done by purposive sampling with resource persons or people who are considered to have the most knowledge of the problems faced in the field such as fishery entrepreneurs, fishermen, apparatus at the village, sub-district and district levels as well as related officials. The data analysis used is according to the research objectives, namely needs analysis and SWOT. The fishing control strategy carried out in the waters of Pohuwato Regency is the approach to managing ship documents, increasing human resources, developing infrastructure and operational costs, improving the fishermen's economy and community skills, law enforcement in the field of marine and fisheries, increasing Pokmakwas in every village and raising public awareness.